Spatial analysis of surplus water risk - Bíró, Tibor; Tamás, János; Lénárt, Csaba; Tomor, Tamás (Acta Agraria Kaposváriensis, 2002)
The surplus water results from a complex process. Its quantity can only be determined through taking numerous factors into consideration. The integration of different geographical information systems allows for the exact evaluation of spatial distribution of the influential factors and the quantification of surplus water, which occurs randomly, under different hydro-meteorological conditions. One method to determine the surplus water risk still used in practice is the yearly mapping of the areas damaged by the water. The objective risk evaluation can also be done through the analysis of the causes. The environmental factors to which surplus water can be assigned (topography, soil, groundwater, vegetation etc.) can be subject to spatial analysis and the randomness of the occurrences can be limited. The results of these procedures are surplus water risk maps of the areas, which can be utilised in land use planning. The risk map of the research site was created with overlaying digital category maps of the determining factors (hydraulic conductivity, water capacity, convexity, critical probability of ground water level and land use).
Keywords: GIS; hydraulic conductivity; water capacity; ground-water; surplus water risk